(untitled) (Journal of Social Sciences Review, 2024)
Mental health problems are more noticeable in university students (Eisenberg et al., 2007); therefore, there is a dire need to study students’ perspectives on protective and risk factors of mental health problems. To explore the university students’ perspectives on protective and risk factors for mental health. The study was conducted in Lahore, a city in Punjab, and the duration of the study was from 14-6-2023 to 14-05-2024. A purposive sample of twenty university students (men: 10, women, 10) with an age range of (18-24) years were recruited in the study. A semi-structured interview guide was developed to explore the participants’ understanding of the mental health problems faced in academic life. The study followed the thematic analysis guidelines given by Braun and Clarke (2006) to explore the key findings. The results of the thematic analysis emerged major themes of risk factors named mental health problems, academic stressors, and socio-emotional stressors in university students. Mental Health problems are i.e. depressive symptoms, stress-related symptoms and anxiety-related symptoms. Socio-emotional stressors are i.e. financial crisis, relationship problems, emotional dysregulation and poor decision-making. At the same time, protective factors are mental health awareness, a positive mindset, social support and academic success. The research findings showed that mental health problems in University students are negatively influenced by stressful life happenings.